The Concept of ‘Uzlah (Self-Isolation) from a Hadith Perspective: An Analysis of Hadith Narrated by Muslim No. 1888. - Muhammad Royyan Faqih Azhary (BAMALA Institute, 2025)
The concept of uzlah (self-isolation) in Islam is often understood dichotomously, either as a praiseworthy spiritual practice or as a neglect of social responsibility. This study aims to analyze the hadith of uzlah narrated by Imam Muslim (no. 1888) comprehensively through a tahlili (analytical) approach, examining the validity of the sanad (chain of narration), the content of the matan (text), and its implications in the contemporary context. Using a descriptive-analytical library research method, this study traces the chain of transmission (sanad), evaluates the credibility of narrators through jarh wa ta'dil procedures, and analyzes the meaning of the text (matan) along with its contextualization. The results show that the sanad of the uzlah hadith is connected (muttaṣil) and authentic (ṣaḥīḥ), with all narrators considered credible. The analysis of the matan reveals that uzlah in Islam is contextual and not absolute. This practice becomes prohibited if it leads to the neglect of family obligations, abandonment of amar ma'ruf nahi munkar (enjoining good and forbidding evil), or mere escape from responsibility. Conversely, uzlah is prescribed in environments characterized by systemic immorality, for temporary spiritual recovery, or in the context of scholarly or educational retreats (khalwat ilmiyah). This study concludes that the hadith of uzlah aligns with maqāṣid al-sharīʿah (the objectives of Islamic law), particularly the principle of ḥifẓ al-dīn (preservation of faith) in emergency situations, and offers a balanced framework for understanding between individual spiritual needs and social responsibilities.